Ativismo LGBT no Facebook: estudo do discurso do Grupo Corpolítica - Silva, Diogo Alves da (2019)
This work aims at a relationship between the LGBT virtual groups of the Federal District and its environment. The way of perceiving, of analytical and contextual analysis, has been more groups in social networks as a reinforcement of online activist activities. Using a technique of netnography, a monitoring was carried out, an end to the understanding as interactions, relations and strategies of the LGBT movement. The object was investigated by the participation of eminent central actors, leadership positions, undergraduate and graduate students. Often, in the figure of an individual, all options are excluded from the lists, that is, a student in a leading position.